Evolution of human oocyte cryopreservation: slow freezing versus vitrification. Issue 6 (December 2016) - Levi-Setti, Paolo Emanuele; Patrizio, Pasquale; Scaravelli, Giulia
Abstract : Purpose of review: The purpose is to determine the efficiency and efficacy of oocyte cryopreservation by slow freezing versus vitrification, recent data collected from the Italian National Assisted Reproductive Technology Register during the period 2009–2014 will be presented and reviewed. The data on oocyte cryopreservation were also compared with the results obtained with embryo cryopreservation and relative IVF with fresh oocytes. Recent findings: During the period 2009–2014 preservation of oocytes by vitrification had a significantly higher survival rate, implantation, and pregnancy rate than slow freezing; however, there are still large variations in success rates among centers in relation to the number of procedures performed. Summary: Vitrification has now become the method of choice for oocyte cryopreservation because of better results than slow freezing, but still requires a more standardized utilization. The transfer of fresh or cryopreserved embryo still shows a statistically significant better performance than transfers with embryos obtained with cryopreserved oocytes. Only in a few centers with much experience in cryopreservation are the results between transfers of frozen embryos or embryos obtained from oocyte cryopreservation comparable.